Empirical analysis on household savings in Malaysia / Nur Liyana Mohamed Yousop …[et al.] - Mohamed Yousop, Nur Liyana; Wan Zakaria, Wan Mohd Farid; Ahmad, Zuraidah; Abdul Manan, Ahmad A'thif (Universiti Teknologi MARA Shah Alam, 2020)
The Malaysian household saving growth has shown weakened patterns from year to year. Low-income level, overspending and black swan economic events result in nosedived household savings. To explain this issue, this study empirically examined factors affecting household savings in Malaysia. The analysis was based on time-series data gathered from World Bank Data, CEIC Data and Department of Statistic of Malaysia from 1970 until 2018. The ordinary least square (OLS) regression analysis was used to examine the significant relationship among dependent variable (household savings, proxy gross domestic savings) and independent variables which consist of interest rate, inflation rate, age dependency ratio, consumption expenditure and income. The findings from this study reveal that the interest rate and household consumption expenditure have significant negative relationships with the household savings, while age dependency ratio, inflation rate and income have insignificant relationships with the household savings.